Health anxiety and cyberchondria among Ege University health science students. (December 2018) - Bati, Ayse Hilal; Mandiracioglu, Aliye; Govsa, Figen; Çam, Olcay
Abstract: It is common among health science students to incorrectly believe that they have contracted certain diseases they have recently studied. This can also be seen in the form of health anxiety and investigating health-related information via the internet. Health anxiety, cyberchondria and affecting factors are determined among health science students. The study was conducted at the faculties of Medicine, Pharmacy, Dentistry and Nursing in 2016–2017 with the participation of 874 students. The data were gathered using a questionnaire as well as health anxiety and cyberchondria severity scales. In the presence of a health problem, 14.2% of students seek health information via the internet. 83.7% use mobile phone to access the internet, ¼ of students conduct health scanning once a week or more. To 65.4%, internet information is correct at medium and above level. No statistically significant difference was found with respect to students' gender, high school, places they lived before, parents' education and scales' scores. The cyberchondria scores of students with health problems are higher in the whole scale and in "distress and mistrust of medical professional" subscales. As the frequency of scanning on the internet increases, the scores of cyberchondria also increase significantly. Medical students had significantly higher scores in "distress, excessiveness and reassurance" subscales. Male students' "mistrust of medical professional and compulsion" subscales scores were also higher. It was determined that the presence of the health problem was effective on the cyberchondria. Identification of somatoform problems like health anxiety and cyberchondria may help to regulate the education program.